Potensi Energi Terbarukan dari Biogas Limbah Ternak Ruminansia Di Kabupaten Sidrap - Purnomo, Nurul; Yusriadi, Yusriadi (Program Studi Peternakan Universitas Muhammadiyah Sidenreng Rappang, 2023)
The increase in the population of ruminants has resulted in an increase in the production of livestock waste which has the potential to be a source of environmental pollutants as well as a potential biogas producer. The study of the biogas potential of ruminant livestock waste in Sidrap Regency was carried out using secondary data from BPS. Biogas potential is calculated by multiplying the ruminant population with the potential for livestock waste production, solid matter content, volatile matter content, and volatile matter biogas production in one year. The potential energy for biogas propulsion from ruminant livestock waste is calculated using the multiplication of the potential for biogas production per year with the methane content of biogas and the energy value of methane gas. The biogas equivalence of LPG gas is calculated by multiplying the biogas potential of ruminant livestock waste by the equivalent per m3 of biogas with LPG. The results of the study show that the biogas potential of ruminant slag waste in Sidrap Regency is 1,071,508.23 m3/year. The potential driving energy of biogas from ruminant livestock waste in Sidrap Regency is 5,400,401.49 kWh/year. The biogas potential of ruminant livestock waste in Sidrap Regency is equivalent to 492.893.79 kg/year LPG. Based on the results of the study, it can be concluded that the potential for renewable energy biogas from ruminant livestock waste in Sidrap Regency is very large.